Analisis ANALISIS IMPLEMENTASI PEMBELAJARAN PROJECT BASED LEARNING DALAM MUATAN IPA DI KELAS 5 SEKOLAH DASAR - Ramadani, Merlisa; Faizal Chan; Violita Zahyuni (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research aims to describe the implementation of Project Based Learning (PjBL) model learning on science content in class 5 of Muara Bulian State Elementary School 13/I. It is hoped that the results of this research can be used as a source of information regarding the implementation of the Project Based Learning (PjBL) learning model in science content in class 5 of the state elementary school 13/I Muara Bulian. Based on the results of the research and discussion, it can be concluded that the analysis of the implementation of project-based learning in science content in class 5 of Muara Bulian State Elementary School 13/I carried out by the class 5C teacher in the material